The investigation of the fatigue failure of passenger carriage draw-hook. (October 2019) - Ulewicz, Robert; Nový, František; Novák, Pavol; Palček, Peter
Abstract: In the presented paper, the failure of the passenger carriage draw-hook is examined. Observation of the crack surfaces revealed the fatigue character of the examined failure. The carefully carried out analysis of the material and draw-hook assembly, together with the FEM, showed that the failure was the result of several contributing factors. To prevent similar failures in the future, it is needed to make significant changes in the relevant standard about prescribing the acceptance conditions, modify the design of the draw-hook and use some of the new advanced steels with increased mechanical properties. Graphical abstract: Unlabelled Image Highlights: The failures of the draw-hooks in railway transport is long-standing problem. The material properties of broken draw-hook meets all standard requirements. The FEM analysis of critical part revealed peak stress near to yield strength. Draw-hook failed due to the small transition radius and the additional bending loading. Wear damage of the linear casing and large difference of wheel diameters of nearby carriages causes bending loading.